Synergetic effects of oxidative and coordinative promotors to increase the yield of a twofold Pauson-Khand reaction - Gleiter, Rolf; Schulte, Jan Hilko; Werz, Daniel B. (European journal of organic chemistry, 2004)
Four medium-sized cyclic diynes (7, 15−17), two cyclic dithiadiynes (18, 19) and two cyclic tetrathiadiynes (20, 21) were starting materials for Pauson−Khand reactions with ethylene and (octacarbonyl)dicobalt under four different conditions: A with 1 equivalent n-butylmethyl sulfide (BMS), B with 7.5 equivalents dimethyl sulfoxide (DMSO), C with 7.5 equivalents DMSO and 1 equivalent BMS and D with 7.5 equivalents DMSO and 7.5 equivalents BMS as additives. In the cases of 7 and 15−17, the yields increased strongly by applying protocol C. For 18−21, no increase in the yields was found under conditions A−D. These differences are discussed and ascribed to intramolecular S−Co interactions in the cases of 18−21. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)
Gesehen am 27.10.2020